English dog expressions: Categorisation, structure, attitude, semantic molecules, and translatability into Arabic - Mohammed Farghal; Ahmad S. Haider (Peoples' Friendship University of Russia (RUDN University), 2023)
The present study aims to examine dog expressions in English in terms of categorisation, structure, attitude, semantic molecules, and translatability. This paper shows that the richness of English dog expressions qualifies the conceptual metaphor HUMANS are DOGS at a status comparable to that of the universal conceptual metaphor HUMANS are ANIMALS. The data in this study consists of 110 English dog expressions, a large sample that may not exhaust the entire corpus. This data is mainly collected from internet sources, dictionaries, linguistic textbooks, and native speakers of English. Based on the analysis of these expressions, the results show that 91.25% map negative dog attributes and habits onto people despite the highly-esteemed position the dog now occupies in Anglo-American cultures. Idiomatic expressions are found to be dominant in the data (72.72%), followed equally by idiomatic comparisons (13.64%) and proverbs (13.64%). While idiomatic comparisons and proverbs are structurally realised uniformly in similes and sentences respectively, idiomatic expressions are varied in structure, which is mostly realised in noun phrases (50%) and verb phrases (43.75%). In terms of semantic molecules, dog expressions are shown to reflect a rich spectrum of source domains. Regarding translatability, only some dog expressions translate formally, while most call for either functional equivalence or paraphrase. To conclude, this paper fills in a gap by systematically investigating English dog expressions from several perspectives. Besides, it is particularly valuable for both non-native English speakers who may not be familiar with many of the dog expressions in the corpus and native English speakers whose lexical competence may fall short of accounting for all the expressions in the data.